Keberagaman Dalam Budaya Organisasi Syariah: Systematic Literature Review Terhadap Konsep, Praktik, Dan Dampaknya Pada Kinerja Organisasi - Jimmi Saputra; Himyar Pasrizal (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the concept, practice, and impact of diversity in Islamic organizational culture through a qualitative approach using the Systematic Literature Review (SLR) method. The study was conducted on 15 articles selected using the PRISMA model from journals indexed by Sinta, Scopus, Springer, and international publishers for the period 2018–2026. The results show that conceptually, diversity in Islamic organizations has not been fully integrated with modern management theory, even though Islamic values ​​have become a strong normative foundation. In practice, diversity is implemented through inclusive recruitment, human resource development based on Islamic values, inclusive leadership, and communication and conflict management that prioritizes deliberation. Diversity also has a positive impact on improving organizational performance, innovation, and social relations, although it has the potential to give rise to conflict if not managed effectively. These findings emphasize the importance of Islamic organizational culture as an integrative mechanism and the need to develop a conceptual model that combines Islamic values ​​and modern diversity theory to support inclusive, adaptive, and sustainable organizations.